Detection of Endocarditis Associated Pili Genes in Enterococcus Faecalis Clinical Isolates - Ayat Ahmed Najm; May Talib Flayyih (Ibn Al-Haitham Journal for Pure and Applied Sciences)
Out of 207 specimens,118 Enterococcus faecalis isolates were obtained from different sources (urine, root canal, wound, vagina, and blood). The commonest sites of infections were the root canal (50.8%), followed by the urinary tract (38.1%), wound (8.4%), and the vagina (2.5%). Urine, root canal, and wound samples from individuals aged 20–40 years old showed the highest prevalence of Enterococcus faecalis isolates, except for the vagina, where those over 40 years old recorded the highest rates of isolates. According to gender, females had the highest prevalence of Enterococcus faecalis isolates in urine, root canal, and vaginal samples, with the exception of the wound source, where males had a higher rate of isolates than females. The antibiotic susceptibility test results indicated that all Enterococcus isolates were resistant to these antibiotics. All Enterococcus isolates (100%) demonstrated resistance to Azithromycin, Clarithromycin, Erythromycin, Doxycycline, Minocycline, Tetracycline, and 64.7% to Gentamicin. On the other hand, 100% of the isolates showed susceptibility to Linezolid, Daptomycin, Teicoplanin, Tigecycline, and Vancomycin, while 58.8% showed susceptibility to Streptomycin, 76.4% to Ciprofloxacin, and 94.1% to Ampicillin. The PCR technique identified the presence of epbA and epbC genes in 28 Enterococcus faecalis isolates. The results of PCR showed that all of the isolates had genes epbA (111bp) and epbC (85bp).